Improvement of Power Quality for Operation of the Grid-Connected Photovoltaic Energy System Considering the Irradiance Uncertainty - Acero J.F.C. (2020)
The quality of electrical energy for connection to the network is sought; as a result, various phenomena that affect the quality of energy occur, identifying the inverter and converter as the equipment responsible for generating these phenomena. Therefore, determining the optimal level of penetration for photovoltaic panels is a vital issue in terms of preventing power quality problems. The methodology is based on the dependence of the total harmonic distortion on the current, solar irradiation, inverter output current, RMS voltage for the grid connection point, and active and non-active power registers. These parameters were calculated using a programming and loop reference frame, simulated with ETAP 16.0.0 software. The results obtained met the criteria established with the energy quality standards for connection to the grid, related to the work of the MPPT converter for each photovoltaic module and the uncertainty of the irradiance. Therefore, low levels of PF can be reduced by increasing the number of modules photovoltaic, since the inverter used is oversized, that is, the system operating with PF capacitive, allowing injection of reactive power in the network. © 2020 IEEE.